Respostas inflamatórias e comportamentais ao uso de canabidiol em um modelo de sickness behavior induzido por lipopolissacáride - Pedro Augusto Lopes Tito (2016)
The Major Depressive Disorder (TDM) affects millions of peoples worldwide, with an annual prevalence estimated between 5 e 9%. Nevertheless, treatment options available has a relative low efficacy, which can be comprehended by the restrict knowledge over the physiopathology of the disease. Recently, several evidences have arisen concerning the role of the immune signaling over the development of TDM. Different animal models are employed in order to reproduce distinct aspects of the disorder, such as Sickness Behavior (SB) model induced by lipopolysaccharide (LPS). Simultaneously, development of new drugs tries to take benefit from these new physiopathology propositions and the endocannabinoid system modulators are an example. Recently discovered and described, this system is active in several brain areas and it is implicated in many intracellular pathways in order to modulate neurotransmission. In this context, we intend to reproduce the SB model and its behavioral features and evaluate the response of the model to a cannabidiol trial. Using LPS, two models of sickness behavior were generated: one with a lower dose (0.11 mg/kg) and another with a higher dose (0.83 mg/kg). Although the lower dose model had a decreased burrow behavior in the burrowing test, the treatment with canabidiol (CBD) have not restored this behavior to baseline. On the other hand, CBD was able restore the alteration in the forced swimming test (FST) in the later. In this model, IL-6 levels in hypothalamus (HT), pre-frontal cortex (CPF) and hipoccampus (HC) were increased in SB and were restored to baseline in CPF and HC. We have also shown a decreased IL-1 and TNF production in CBD treated mice in HC. Although animal models are useful tools to human diseases study, it is hard to reproduce all the disease characteristics. The FST has a good predictive validity, making it useful to foresee antidepressants candidates. Applying the SB as an immune model of TDM, increases the specificity of the analysis, restricting the therapeutic effects within the set of alterations defined by the model